1997
DOI: 10.1002/etc.5620161016
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and metallothionein response in the asiatic clam (Corbicula fluminea) after experimental exposure to cadmium and inorganic mercury

Abstract: Abstract-The involvement of metallothioneins (MTs) in cadmium (Cd) and inorganic mercury (Hg [II]) bioaccumulation by the freshwater bivalve Corbicula fluminea was experimentally investigated after 0, 15, 30, and 45 d of exposure from the water column source. Three levels of contamination were studied for each metal: 0, 5, and 35 g Cd/L and 0, 1.45, and 5 g Hg/L, with two replicates per condition. Forty eight experimental units (EUs) were conducted simultaneously. The mollusks were fed twice a week by addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(28 citation statements)
references
References 24 publications
1
24
0
3
Order By: Relevance
“…The choice of these two contamination levels was a compromise between values found in the natural environment, which are for the most part much lower, and the experimental constraints, especially the relationships between exposure periods, bioaccumulated concentrations, and capacities of trophic transfer. Note however that these concentrations are much lower than the majority of experimental approaches set up using this metal (Torreblanca et al, 1992;Baudrimont et al, 1997;Franchet, 1999). The ratio of 10 between the two chemical forms is similar to results obtained in several lakes, showing that MMHg concentrations in freshwater systems are between 5 and 20% of the concentration of total Hg in the dissolved fraction (Bloom et al, 1991;Watras et al, 1994).…”
Section: Methods For Hg Contamination Of the Water Columnsupporting
confidence: 72%
“…The choice of these two contamination levels was a compromise between values found in the natural environment, which are for the most part much lower, and the experimental constraints, especially the relationships between exposure periods, bioaccumulated concentrations, and capacities of trophic transfer. Note however that these concentrations are much lower than the majority of experimental approaches set up using this metal (Torreblanca et al, 1992;Baudrimont et al, 1997;Franchet, 1999). The ratio of 10 between the two chemical forms is similar to results obtained in several lakes, showing that MMHg concentrations in freshwater systems are between 5 and 20% of the concentration of total Hg in the dissolved fraction (Bloom et al, 1991;Watras et al, 1994).…”
Section: Methods For Hg Contamination Of the Water Columnsupporting
confidence: 72%
“…Sulfur donors, such as MT and other metal-binding proteins, have been found in digestive cells of the digestive diverticula, podocytes, and nephrocytes, as well as in migrating hemocytes and phagocytes (named pore cells or brown cells, depending on the species), where metals such as Cd, Cu, and Fe (class "b" and some borderlines) are accumulated in lysosomes Mason et al, 1984;Marigómez et al, 1990aMarigómez et al, , 1995Janssen and Dallinger, 1991;Bebianno and Langston, 1992;Carpene, 1993;Rubio et al, 1993;Soto et al, 1996a,b;Baudrimont et al, 1997;High et al, 1997).…”
Section: Cells Binding Metals By Sulfur Donorsmentioning
confidence: 97%
“…C. fluminea seems to be a very interesting species from an ecotoxicological point of view because it has some appealing characteristics that could justified its use in this kind of studies, namely: i) this species has become a major component of benthic communities in several lotic and lentic habitats in different regions of the world and, thus, it has a wide spatial distribution; ii) it may be found in both pristine and polluted environments iii) nowadays presents a very strong invasive dynamics in rivers, channels and lakes where it reaches very high abundance (Phelps 1994, Sousa et al 2008; iv) this bivalve is easily maintained in the laboratory for several months and may be transplanted into field conditions using caging procedures (Cataldo et al 2001a); v) this species has a great filtration capacity allowing the uptake of large amounts of pollutants, vi) several field studies have shown that C. fluminea is a good bioindicator of heavy metals or other contaminants (Doherty 1990, Inza et al 1997, Cataldo et al 2001b and vii) the size of adults makes possible the dissection and separation of the main organs allowing specific analysis. The combination of all these traits and its ability to bioaccumulate and bioamplify several contaminants make C. fluminea a very convenient model in ecotoxicology (Way et al 1990, Bassack et al 1997, Baudrimont et al 1997aand b, 2003, Inza et al 1997, Narbonne et al 1999, Tran et al 2001, Cataldo et al 2001aand b, Achard et al 2004). Additionally, due to their ubiquitous distribution, this species can serve as a basis of worldwide comparisons of environmental monitoring data in freshwater ecosystems as the same manner as Mytilus spp.…”
Section: Positive Effects Negative Effectsmentioning
confidence: 99%